1985
DOI: 10.1111/j.1440-1827.1985.tb00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytes in Odontogenic Keratocyst

Abstract: Melanocytes in odontogenic keratocyst (OKC) were studied histopath‐ologically. As a result, melanocytes were observed within the basal layer of lining epithelium in five of 47 cases with OKC, with the overall prevalence being 10.6 per cent. Although no conclusion could be drawn from the present examination as to the origin of melanocytes in OKC, its possible histogenesis was discussed. ACTA PATHOL. JPN. 35: 899–903, 1985.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The racial factor may play an important one in pigmented odontogenic lesions, since most patients with pigmented odontogenic lesions are Asian or Black (7,(8)(9)(10)(11)(12)(13)(14)(15). However, the limited number of cases does not give any statistical value to the data.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The racial factor may play an important one in pigmented odontogenic lesions, since most patients with pigmented odontogenic lesions are Asian or Black (7,(8)(9)(10)(11)(12)(13)(14)(15). However, the limited number of cases does not give any statistical value to the data.…”
Section: Discussionmentioning
confidence: 87%
“…In another series of 278 odontogenic keratocysts, only one patient, who was an American Black, exhibited melanin-pigmentation. In a study of 47 Japanese patients with odontogenic keratocysts, we found melanocytes and/or melanin-pigment in five patients (8). Only one case of pigmented odontogenic keratocyst was reported in a White patient (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few reports on invasive SCC or intraepithelial squamous neoplasia with melanocytic hyperplasia, namely pigmented SCC, have been reported in certain organs, such as skin, oral mucosa, nasal cavity and uterine cervix (1)(2)(3)(4). The squamous epithelium of KCOT usually does not contain melanocytes, however, cases of pigmented KCOT have been documented, albeit extremely rarely (5)(6)(7)(8). In the present study, we described an additional case of pigmented KCOT and review the clinicopathological features of this extremely rare lesion.…”
Section: Introductionmentioning
confidence: 99%
“…These patients were of West Indian and African origins, respectively (Table I). However, Takeda et al (7) reported that the prevalence of pigmented KCOT was 10.6% (5/47 cases) in the Japanese population and this difference in frequency of pigmented KCOT may be related to ethnicity (7). Takeda et al (7) reported a series of pigmented KCOT and they described two distinct histopathological patterns of this lesion.…”
mentioning
confidence: 99%